Reformasi Pendidikan Islam Berbasis Pesantren Modern - Sirajun Nasihin (PALAPA, 2017)
This paper aims to describe the concepts of Islamic education reform based on modern pesantren both from the perspective of experts and referring to the prevailing laws and regulations. In it the author presents; understanding, pattern, and urgency of Islamic education reform based on modern pesantren with the support of data collected using literature review methods either in the form of books or papers and journals downloaded through the internet. From several views that have been collected, the authors conducted a qualitative data analysis and drew the conclusion that the reform of Islamic education based on modern pesantren in the context of this era is absolutely necessary because this education system that can elaborate between rational intelligence, emotional and spiritual integrally so that it can bear output educational, moral, creative, and always able to put themselves in all situations of the nation without having to change its identity as a muslim Indonesia who berpencasila who can realize national goals as embodied in the opening of the 1945 Constitution.